PENGAJARAN BAHASA DAN BUDAYA INDONESIA UNTUK MAHASISWA KANDA UNIVERSITY JAPAN - Komara Mulya; Frida Philiyanti; Viana Meilani Prasetio; Nia Setiawati; Eva Jeniar Noverisa; Asep Supriyana; Dian Herdiati; Muhammad Ali Hamdi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract This Community Service (P2M) has the title: Teaching Indonesian Language and Culture for Kanda University Japan Students. The implementation of this service activity is a collaboration between the teaching staff of the Japanese Language, Indonesian Language and Music Education Study Program, Faculty of Languages ​​and Arts, Jakarta State University who collaborate with teaching staff at Kanda University International Studies (KUIS), especially those who teach in the expertise program Indonesian. The aim of P2M is to provide an understanding of the development and dynamics of the Indonesian language as well as the development of Indonesian culture. The methods used in this PPM are online seminars and direct face-to-face learning with Kanda University students. The results obtained from P2M are that in learning Indonesian, Kanda University students seem enthusiastic about learning Indonesian, but still seem to have difficulty understanding Indonesian language material in a song. This can be seen from the fact that there are still many who have not been able to fill in or answer the gap questions given. Meanwhile, when the traditional musical instrument angklung was introduced, the students were very enthusiastic about playing it and managed to play several songs with the angklung. During the first song, they couldn't realize the sound of the angklung he was playing because the song was in regional Indonesian. However, when playing Japanese songs, they began to realize that angklung could be played for Japanese songs. Abstrak Pengabadian pada Masyarakat (P2M) ini mengangkat judul: Pengajaran Bahasa dan Budaya Indonesia untuk Mahasiswa Kanda University Japan. Pelaksana kegiatan pengabdian ini adalah kolaborasi antara staf pengajar Program Studi Pendidikan Bahasa Jepang, Bahasa Indonesia dan Seni Musik, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta yang bekerja sama dengan staf pengajar di Kanda University International Studies (KUIS), khususnya yang mengajar pada program keahlian bahasa Indonesia. Adapun tujuan dari P2M ini adalah untuk memberikan pemahaman tentang perkembangan dan dinamika bahasa Indonesia serta perkembangan budaya Indonesia. Metode yang digunakan dalam P2M ini adalah seminar online dan pembelajaran tatap muka langsung dengan mahasiswa Kanda University. Hasil yang didapat dari P2M ini adalah dalam pembelajaran bahasa Indonesia, para mahasiswa Kanda University terlihat antusian mengikuti pembelajaran bahasa Indonesia, namun masih terlihat kesulitan memahami materi Bahasa Indonesia dalam sebuah lagu. Hal ini terlihat dari masih banyak yang belum bisa mengisi atau menjawab soal rumpang yang diberikan. Sementara itu, saat diperkenalkan alat musik tradisional angklung, para mahasiswa pun sangat antusias memperagakannya dan berhasil memainkan beberapa lagu dengan angklung. Pada saat lagu pertama, mereka belum bisa menyadari bunyi angklung yang dimainkannya karena lagu berbahasa daerah di Indonesia. Akan tetapi, pada saat memainkan lagu Jepang, mereka mulai menyadari bahwa angklung dapat dimainkan untuk lagu Jepang.